THE IMPACT OF FAMILY AND INDIVIDUAL FACTORS ON 4TH GRADE STUDENTS’ SELF-CONFIDENCE IN READING LITERACY: RESULTS FROM PIRLS 2016 - Geske, Andrejs; Kampmane, Kristine; Ozola, Antra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The self-confidence of a child and an adult is associated with performance and achievement results. It is well-studied, and the correlation has been proved that higher self-efficacy leads to higher achievements and performance, including better performance in reading literacy. It is also known that both a family and a home environment have a tremendous impact on the child’s development and academic performance. This article focuses on the 4thgraders and their family factor impact on the development of a child’s self-confidence and concepts related to self-confidence.The purpose of this article is to define concepts that are closely related to self-confidence and to identify family factors that influence students’ self-confidence. The research question is as follows: which family and individual factors impact students’ self-confidence in reading?Authors of the article used a linear regression and correlation analysis of the data from the IEA’s PIRLS 2016 study. The data from Latvia and seven countries of comparison were analysed.The results of data analysis showed that, in general, the 4th graders’ self-confidence in reading literacy is higher if they come from a household where a computer or a tablet with Internet connection is available and if students like to chat using a mobile device. Parents’ attitudes to reading and the students’ readiness for 1st grade promote higher self-confidence as well.